The Potentialof “Uwi” Plant (Dioscoreasp.) as a Non-Rice Alternative Food Material - Wuryantoro Wuryantoro (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2020)
“Uwi plant (Dioscorea sp.) as a type of tuber has the potential to support food diversity and food security in the future because it is very tolerant of being planted in all kinds of land including upland. In Indonesia, even in the world, the potential for dry land is very wide and has not been maximally utilized. This study aims to obtain